Introduction of lymphadenopathy associated virus or human T lymphotropic virus (LAV/HTLV-III) into the male homosexual community in Amsterdam. Issue 1 (February 1986) - Coutinho, R A; Krone, W J; Smit, L; Albrecht-van Lent, P; van der Noordaa, J; Schaesberg, W; Goudsmit, J
Abstract : To establish when lymphadenopathy associated virus or human T lymphotropic virus (LAV/HTLV-III) was introduced into the Netherlands, we studied a cohort of homosexual men who participated in a hepatitis B vaccine efficacy study between 1980 and 1982. On entry into the study (November 1980 to December 1981) five (0.7%) out of 685 participants were found to have antibodies to LAV/HTLV-III, and during follow up 15 seroconversions were detected among the 680 who had been seronegative initially (end point attack rate 3%). LAV/HTLV-III was not transmitted by the heat inactivated hepatitis B virus (HBV) vaccine used. Anal sexual contact and antibodies to cytomegalovirus (CMV) were found to correlate with seropositivity or seroconversion for LAV/HTLV-III. Six out of 15 men who seroconverted reported a mononucleosis like illness, but three of them had other concurrent virus infections. To date, only one of the 20 seropositive men has developed the acquired immune deficiency syndrome (AIDS), three years after his seroconversion. This study shows that the introduction of LAV/HTLV-III into the Dutch male homosexual community took place at the end of the 1970s, a few years before the first case of AIDS in a native Dutchman.